Sustainable business digital technology-based model: BikePoa case study as an example - Levrini, Gabriel Roberto Dellacasa; Nique, Walter Meucci (Revista de Administração da UFSM, 2019)
Environmental disasters attributed to global warming, strong media pressures towards an ecologically sustainable consumption, give path to alternative forms of green and sustainable consumption, like the sharing economy, a rising pattern in consumption behavior, based on accessing and reusing products to utilize idle capacity. The sharing economy holds the potential to bring effectiveness toward widespread sustainable business practices. The research objective is to propose a sustainable business technology-based model using technology as mediator among the shared economy agents under the lens of Actor Network Theory (ANT). We have chosen, as a sample, BikePoa bicycle sharing system has 40 stations and more than 2,000 bikes, throughout the city of Porto Alegre, in Brazil. The research methodology followed Kozinets’s (2006) participant-observational netnography. It was done 23 personal interviews with users and 7 with employees’ provider, and later through Google Docs 251 questionaries’ were selected. Findings point for two different factors consumers’ inductors and providers ‘connection factors.